Music Theory Learning in Performing Arts Education: Pedagogical and Aesthetic Perspectives - Tengku Ritawati; Ali Darsono (Westscience Press, 2026)
Music theory learning is a conceptual foundation in performing arts education, but in practice it is often perceived as an abstract subject that is detached from students' artistic experiences. This study aims to examine music theory learning from a pedagogical and aesthetic perspective and to formulate principles for its development based on a praxial music education framework and humanistic pedagogy. This study uses a descriptive qualitative approach based on classes of students in the performing arts education study program, with the researcher acting as a practitioner-researcher who conducts systematic observation and reflection on the learning process. Data were collected through classroom observation, student reflective journals, semi-structured interviews, and analysis of learning documents, then analyzed using thematic analysis techniques. The results showed that the integration of theoretical concepts with musical practice, aesthetic reflection, pedagogical dialogue, the use of digital technology, and cultural relevance transformed music theory from procedural knowledge into musical meaning-making practice. This approach improves students' aesthetic sensitivity while strengthening the construction of their professional identity as prospective art educators. This study confirms that music theory learning is designed in an integrative and contextual manner as an epistemic and humanistic practice, transcending its traditional function as mere transmission of structural knowledge.